Theoretical and Applied Principles of Supply Chain Management under Crisis Economic Conditions: Strategic Aspect - Zaverbnyj, A.; Pushak, H. (Економічний вісник Донбасу, 2022)
The article highlights the main methodological and strategic aspects of supply chain management under crisis economic conditions. The authors defined the essence of the concept of «supply chain». In the supply chain structure, it is possible to distinguish complete logistics chains, which, in turn, contain all key links and stages of the reproduction process, starting from raw material sources and ending with final consumers. New tasks related to the formation of rational logistics chains, supply chains and the construction of effective systems of their management have been analyzed. Comparative characteristic of supply chain management models is given. The key characteristic features include structural and conceptual, the level of interconnection with the enterprise strategy, the breadth of the set of activities, intra-organizational connections, inter-organizational connections, value forming factors, information support, etc. A new vision of economic transformation is established in logistics practice. Integration into global production networks will allow countries (especially Ukraine) to reveal their comparative advantages by focusing on specific tasks and industries. Modern production systems, which have become the end result of the dynamism of production factors, distribution and production networks, have been studied. The critical problems regarding the choice of existing corporate strategies by enterprises for their further effective expansion have been highlighted. The strategies available in the global economy have been analyzed, their advantages and disadvantages have been highlighted. In general, to establish the cumulative impact of all business processes on the level of performance of the supply chain, which will allow us to approach the measurement of the level of their synergistic effect, it is necessary to ensure constant monitoring of indicators in two areas: process and system. Under crisis economic conditions (in particular, instability of markets, destruction of well-established supply chains, in particular, due to military actions), there is a need for a quick response, complete modernization, and adaptation of the proposed logistics services throughout the supply chain. It has been proposed to form and offer a market of the latest, perfect, adaptive services to clients, which will allow balancing the unpredictability of the market with the need to obtain a stable, growing level of profitability. У статті висвітлено основні методологічні стратегічні аспекти управління ланцюгами поставок за кризових умов господарювання. Автори визначили сутність поняття «ланцюг поставок». У структурі ланцюга поставок можна виділити повні логістичні ланцюги, які, у свою чергу, містять усі ключові ланки та етапи процесу відтворення, починаючи від джерел сировини і закінчуючи кінцевими споживачами. Проаналізовано нові завдання щодо формування раціональних логістичних ланцюгів, ланцюгів поставок та побудови ефективних систем управління ними. Наведено порівняльну характеристику моделей управління ланцюгами поставок. До ключових характерних особливостей відносяться структурно-концептуальні, рівень взаємозв’язків зі стратегією компанії, широта спектру діяльності, внутрішньоорганізаційні зв’язки, міжорганізаційні зв’язки, чинники формування цінностей, інформаційне забезпечення тощо. У практиці логістики утверджується нове бачення економічної трансформації. Інтегрування до глобальних виробничих мереж дозволить країнам (особливо Україні) виявити свої порівняльні переваги, зосередившись на конкретних завданнях і галузях. Досліджувалися сучасні виробничі системи, які стали кінцевим результатом динамізму виробничих факторів, розподільчих і виробничих мереж. Висвітлено критичні проблеми щодо вибору підприємствами існуючих корпоративних стратегій для їх подальшого ефективного розширення. Проаналізовано наявні в глобальній економіці стратегії, висвітлено їх переваги та недоліки. Для встановлення сукупного впливу всіх бізнес-процесів на рівень ефективності ланцюга поставок, що дозволить підійти до вимірювання рівня їх синергічного ефекту, необхідно забезпечити постійний моніторинг показників за двома напрямками: процес і система. У кризових економічних умовах (нестабільність ринків, руйнування налагоджених ланцюгів поставок, зокрема, через військові дії) виникає потреба у швидкому реагуванні, повній модернізації та адаптації пропонованих логістичних послуг по всьому світу. ланцюг поставок. Пропонується сформувати та запропонувати клієнтам ринок новітніх, досконалих, адаптивних послуг, що дозволить збалансувати непередбачуваність ринку з необхідністю отримання стабільного, зростаючого рівня прибутковості.